Tibial Nerve Branches in Relation to the Tarsal Tunnel: A Cadaveric Study. Issue 4 (November 2022) - Mattos, Ivan; Ubillus, Hugo A.; Campos, Gustavo; Soares, Sérgio; Azam, Mohammad T.; Kennedy, John G.
Category: Hindfoot; Ankle Introduction/Purpose: Tarsal tunnel syndrome (TTS) is typically caused by an anatomical variant or mechanical compression of the tibial nerve (TN). It is critical then to understand the anatomy of the TN in relation to the tarsal tunnel to understand this condition more fully. Methods: 40 lower-leg specimens were obtained. Dissection started 20 centimeters proximal to the DellonMcKinnon (DM) line towards the medial aspect of the naviculo-cuneiform joint distally. Anteriorly, dissection began at the tibio-talar medial gutter until the medial aspect of the Achilles tendon posteriorly. The plantar aspect extended from medial to lateral within the parameters previously described, ending at the level of the second metatarsal. Results: The flexor retinaculum had a denser consistency in 22.5% of the cases and the average length was 51.9 mm. The flexor retinaculum as an independent structure was absent and 77.2% of cases as an undistinguished extension of the crural fascia. The lateral plantar nerve (LPN) and abductor digiti minimi (ADM) nerve shared the same origin in 80% of cases, 34.5% bifurcated proximal to the DM line, 31.2% distally and 34.3% at the same level. The medial calcaneal nerve (MCN) emerged proximal to the DM line in 100% of specimens. The medial plantar nerve (MPN) has its origin proximal to the DM line in 95% of cases. Conclusion: The flexor retinaculum is an extension of the crural fascia and not an independent structure. The LPN and ADM have the same origin in most cases and this presents as an important finding that must be studied in detail for clinical correlations between the motor ADM and sensory LPN affections. Finally, the branches of the MCN and MPN are the most constant in their distribution and proximal origin in relation to the DellonMcKinnon line.